Strategi Marketing Public Relations Agrowisata Grand Sondokoro dalam Membangun Brand Awareness melalui Instagram - Meutia Rahmadhania Fatika; Wisudawanto, Rahmat; Ningsih Rahayu Putri, Sofia (JURNAL KOMUNITAS, 2024)
Strategy is an important component to achieve goals according to the vision and mission of a company. The effort cannot be separated from the important role of public relations (PR). Grand Sondokoro Agrotourism is one of the historical tourist attractions in Karangayar Regency, Central Jave, operating since 2007 which utilizes and develops the assets of the Tasikmadu sugar factory which are no longer in use. The existence of business competition in the tourism sector makes business people think hard to create the best strategy. The aim of the research was to explain the strategy carried out by Grand Sondokoro Public Relations in building brand awareness by utilizing Instagram using three ways strategy analysis, which consists of pull, push and pass strategy. Data collection techniques used interviews, documentation, observation. Of the 3 strategies that had been implemented by Grand Sondokoro Public Relations, there were two problems. The first problem was at the brand recognition level, namely that followers did not fully understand the uploads presented and need to provide information such as clear captions or other information that described the uploads. The second problem was brand recall, namely the lack of communication or conversations with followers on social media. sustainably.